Faktor-faktor yang Mempengaruhi Pemberian Opini Audit Going Concern: Pertumbuhan Perusahaan, Ukuran Perusahaan dan Opini Audit Tahun Sebelumnya - Ainun Basita; Cris Kuntadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Going concern audit opinion is an opinion issued by the auditor to determine whether a company can maintain the survival of its company, going concern audit opinion is very useful for investors to help the investment decision making process. This article is conducted by conducting a literature study of various studies that have been conducted. This article reviews the factors that influence the provision of going concern audit opinion, namely company growth, company size and previous year's audit opinion, a study of tax accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) company growth affects the provision of going concern audit opinion; 2) company size affects the provision of going concern audit opinion; and 3) the previous year's audit opinion affects the provision of going concern opinion.